Mating frequency of the Guatemalan potato moth Tecia solanivora (Lepidoptera: Gelechiidae) - RINCÓN, DIEGO FERNANDO; GARCÍA-G., JAVIER (Revista Colombiana de Entomología, 2007)
The Guatemalan potato moth Tecia solanivora is considered one of the most serious pests of the potato crop in Colombia. Currently, most efforts for controlling populations of the insect are focused in the development of methodologies to disrupt its reproduction. Therefore, it is necessary to understand the behavior and factors affecting the reproductive potential of T. solanivora. In this study the mating frequency of T. solanivora and its effect on adult reproductive potential was determined. To determine the mating frequency of females, two experiments were conducted in which males and females of T. solanivora were confined in different proportions. To establish the mating frequency of males, two experiments were carried out. In the first, one virgin female was offered daily to each male confined individually. In the second, different numbers of females were offered to an individual male. Most females mate just once, and those females that mate more than once do not obtain a significant benefit in their reproductive potential or in their longevity. Males mate an average of five times depending on the number of females available. A significant decline in male reproductive potential with increasing number of copulations was observed, although they seem to have the capacity to dose their ejaculation depending on the number of females available. The viability of the implementation of methodologies based on the mass capture of males for the control of T. solanivora is discussed.